Pneumonia - Sotgiu, Giovanni; Rijkers, Ger.; Pelton, Stephen Ira.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Pneumonia is the only journal to focus exclusively on pneumonia. Publishing original research, case reports, reviews, commentaries and correspondence, Pneumonia provides an international forum for the exchange of knowledge by scientists and clinicians involved in studying the etiology and pathogenesis of pneumonia, as well as its diagnosis, epidemiology, treatment and prevention. The journal's scope extends to research on lung infections and diagnosis, inflammation and immunity, microbial pathogenesis and viral-bacterial interactions. Cutting-edge research, insightful reviews and dedication to the community make Pneumonia an essential resource for clinicians, researchers, respirologists and allied professionals involved with infectious diseasea.
Keywords: Respiratory organs$1 (BDiseases.s; Diseases; Pneumology; Diseases